2020
DOI: 10.1136/bjophthalmol-2020-316245
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of widefield swept-source optical coherence tomography angiography with ultra-widefield colour fundus photography and fluorescein angiography for detection of lesions in diabetic retinopathy

Abstract: AimsTo compare widefield swept-source optical coherence tomography angiography (WF SS-OCTA) with ultra-widefield colour fundus photography (UWF CFP) and fluorescein angiography (UWF FA) for detecting diabetic retinopathy (DR) lesions.MethodsThis prospective, observational study was conducted at Massachusetts Eye and Ear from December 2018 to October 2019. Proliferative DR, non-proliferative DR and diabetic patients with no DR were included. All patients were imaged with a WF SS-OCTA using a Montage 15×15 mm sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 25 publications
4
66
0
1
Order By: Relevance
“…NVCs not identified on FA and identified on WF-OCTA (25%) consisted of combined small NVCs with little leakage only detectable on WF-OCTA and ILM segmentation errors generating false positives [86]. As already mentioned, Cui et al [80] reported similar results with comparable detection rates of NVC obtained with WF-OCTA and UWF-FA.…”
Section: Additional Observationssupporting
confidence: 57%
See 1 more Smart Citation
“…NVCs not identified on FA and identified on WF-OCTA (25%) consisted of combined small NVCs with little leakage only detectable on WF-OCTA and ILM segmentation errors generating false positives [86]. As already mentioned, Cui et al [80] reported similar results with comparable detection rates of NVC obtained with WF-OCTA and UWF-FA.…”
Section: Additional Observationssupporting
confidence: 57%
“…Furthermore, this group showed that WF-OCTA detected neovascularization in 88.6% of cases compared to the 72.2% of clinical examination, proving the value of WF-OCTA as an important complementary tool to clinical examination [67,79]. The work of Cui and collaborators [80] reinforced again the significantly superior detection rates of NVE with isolated WF-OCTA when compared to ultra-widefield CFP (UWF-CFP), and found similar detection rates when comparing WF-OCTA to ultra-widefield FA (UWF-FA).…”
Section: Nvementioning
confidence: 90%
“…The increased area represents approximately 80 degrees of the total retina, which is still significantly less than the 200 degrees visualized by UWF-CI and UWF-FA imaging. However, despite the smaller area, WF-OCTA can detect over 95% of all neovascularization (NV) detected on UWF-FA [ 57 , 58 , 59 , 60 , 61 ]. WF-OCTA also has the added advantage of using the vitreoretinal interface (VRI) angio slab to improve detection rates of neovascularization [ 62 ].…”
Section: Wide Field Optical Coherence Tomography Angiography (Wf-octa) Quantitative Metricsmentioning
confidence: 99%
“…Ці інтраретинальні ділянки, які представлені звивистими, малодиференційованими дрібними повнокровними капілярами і венулами, об'єднують в одну клінічну ознаку -ІРМА [28]. Їх вираженість порівняно зі стандартною фотографією хоча б однієї зони також є одним з критеріїв при оцінці ступеня тяжкості ДР [29]. Висновки 1.…”
Section: клінічна офтальмологія / Clinical Ophthalmologyunclassified